Dual-Task in Large Perceptual Space Reveals Subclinical Hemispatial Neglect. (27th November 2020) - Villarreal, Sanna; Linnavuo, Matti; Sepponen, Raimo; Vuori, Outi; Jokinen, Hanna; Hietanen, Marja
Abstract: Objective: Both clinically observable and subclinical hemispatial neglect are related to functional disability. The aim of the present study was to examine whether increasing task complexity improves sensitivity in assessment and whether it enables the identification of subclinical neglect. Method: We developed and compared two computerized dual-tasks, a simpler and a more complex one, and presented them on a large, 173 × 277 cm screen. Participants in the study included 40 patients with unilateral stroke in either the left hemisphere (LH patient group, n = 20) or the right hemisphere (RH patient group, n = 20) and 20 healthy controls. In addition to the large-screen tasks, all participants underwent a comprehensive neuropsychological assessment. The Bells Test was used as a traditional paper-and-pencil cancellation test to assess neglect. Results: RH patients made significantly more left hemifield omission errors than controls in both large-screen tasks. LH patients' omissions did not differ significantly from those of the controls in either large-screen task. No significant group differences were observed in the Bells Test. All groups' reaction times were significantly slower in the more complex large-screen task compared to the simpler one. The more complex large-screen task also produced significantly slower reactions to stimuli in the left than in the right hemifield in all groups. Conclusions: The present results suggest that dual-tasks presented on a large screen sensitively reveal subclinical neglect in stroke. New, sensitive, and ecologically valid methods are needed to evaluate subclinical neglect.